Critical care scientists: Role, training and future directions. (February 2021) - Fowler, Natalie; Ali, Raashid; Bannard-Smith, Jonathan; Jennings, Claire; Playfor, Stephen; Pruski, Michal
Critical care scientists are a little known but increasingly prominent group of professionals, included in both the government-run Modernising Scientific Careers initiative and 2019 Guidelines for the Provision of Intensive Care Services. This article outlines the role of critical care scientists, their training programme and potential future directions for the role. A wider appreciation and acknowledgement of the critical care scientist's role within the multi-disciplinary team will allow critical care units to fully understand the potential benefits that may be brought to patient care and service delivery.